Immunomodulatory Protein from Ganoderma microsporum Induces Pro-Death Autophagy through Akt-mTOR-p70S6K Pathway Inhibition in Multidrug Resistant Lung Cancer Cells - Chiu, Ling-Yen; Hu, Ming-E; Yang, Tsung-Ying; Hsin, I-Lun; Ko, Jiunn-Liang; Tsai, Kan-Jen; Sheu, Gwo-Tarng (PloS one, 2015)
Chemoresistance in cancer therapy is an unfavorable prognostic factor in non-small cell lung cancer (NSCLC). Elevation of intracellular calcium level in multidrug resistant (MDR) sublines leads to sensitization of MDR sublines to cell death. We demonstrated that a fungal protein from Ganoderma microsporum, GMI, elevates the intracellular calcium level and reduces the growth of MDR subline via autophagy and apoptosis, regardless of p-glycoprotein (P-gp) overexpression, in mice xenograft tumors. In addition, we examined the roles of autophagy in the death of MDR A549 lung cancer sublines by GMI, thapsigargin (TG) and tunicamycin (TM) in vitro. Cytotoxicity of TG was inhibited by overexpressed P-gp. However, TM-induced death of MDR sublines was independent of P-gp level. Combinations of TG and TM with either docetaxel or vincristine showed no additional cytotoxic effects on MDR sublines. TG- and TM-mediated apoptosis of MDR sublines was demonstrated on Annexin-V assay and Western blot and repressed by pan-caspase inhibitor (Z-VAD-FMK). Treatment of MDR sublines with TG and TM also augmented autophagy with accumulation of LC3-II proteins, breakdown of p62 and formation of acidic vesicular organelles (AVOs). Inhibition of ATG5 by shRNA silencing significantly reduced autophagy and cell death but not apoptosis following TG or TM treatment. GMI treatment inhibited the phosphorylation of Akt/S473 and p70S6K/T389. Interestingly, the phosphorylation of ERK was not associated with GMI-induced autophagy. We conclude that autophagy plays a pro-death role in acquired MDR and upregulation of autophagy by GMI via Akt/mTOR inhibition provides a potential strategy for overcoming MDR in the treatment of lung cancers.